Exploring ribosome composition and newly synthesized proteins through proteomics and potential biomedical applications - Stastna, Miroslava; Gottlieb, Roberta A; Van Eyk, Jennifer E (Expert review of proteomics, 2017)
Protein synthesis is the outcome of tightly regulated gene expression which is responsive to a variety of conditions. Efforts are ongoing to monitor individual stages of protein synthesis to ensure maximum efficiency and accuracy. Due to post-transcriptional regulation mechanisms, the correlation between translatome and proteome is higher than between transcriptome and proteome. However, the most accurate approach to assess the key modulators and final protein expression is directly by using proteomics. Areas covered: This review covers various proteomic strategies that were used to better understand post-transcriptional regulation, specifically during and early after translation. The methods that identify both regulatory proteins associated with translational components and newly synthesized proteins are discussed. Expert commentary: Emerging proteomic approaches make it possible to monitor protein dynamics in cells, tissues and whole animals. The ability to detect alteration in protein abundance soon after their synthesis enables earlier recognition of disease causing factors and candidates to prevent/rectify disease phenotype.
Keywords: proteomika; ribozomy; Post-transcriptional regulation; AHA; Gene Expression Regulation; non-canonical amino-acid labeling; translation; proteosyntéza; Protein Biosynthesis; regulace genové exprese; newly synthesized proteins; Proteomics; zvířata; dynamic proteomics; fluorescent imaging of synthesized proteins; biomedicínský výzkum; mass spectrometry; ribosomes; Ribosomes; Biomedical Research; Animals